Legislative regulation of oil and gas facilities in Iraqi administrative law - Alshamaa, Huda A.; Hamza, Waleed M. (Journal of Petroleum Research and Studies, 2023)
In this study, we examined the comparative systems of countries known worldwide for their scientific, technical and administrative progress in the field of hydrocarbon resource exploitation, such as the Kingdom of Norway, the United Arab Emirates, the Kingdom of Saudi Arabia, and the State of Qatar. Distinguish between directing the oil policy, which must be carried out by a higher authority in the state, and managing oil operations, which represent the practical and executive side in the exploitation of gas and oil resources. As for managing oil revenues, which must be carried out independently and by an independent body. Each of these topics has its own management style.